Effect of Epichlorohydrin on the DNA and RNA of Growing Wheat Seedlings (Biological Sciences - PJSIR, 2022)
The dishes were kept covered in dark place for 4 days atroom temperature, after interval of24 hrs, one seed was takenfrom each pctridish and crushed in mortor with pestle in coldmethanol. This process was carried out for all seeds individuallyand the materials was filtered separately.